2004
DOI: 10.1002/jcb.20071
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid quercetin decreases osteoclastic differentiation induced by RANKL via a mechanism involving NFκB and AP‐1

Abstract: Flavonoids are micronutrients widely present in food of plant origin. They have been attributed pharmacological properties such as anticancer and prevention of age-related pathologies. It has been recently hypothesized that flavonoids increase bone mass and prevent osteoporosis. However, little is known about the in vitro effects of flavonoids on osteoclast activities. We investigated the effects of quercetin, one of the most commonly occurring flavonoids, on osteoclast differentiation which is a critical dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
114
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 50 publications
6
114
0
1
Order By: Relevance
“…(7,(10)(11)(12)33,34) In another study, the flavanone glycoside, naringin, protected against ovariectomy-induced bone loss, potentially mediated through ligand-independent activation of estrogen receptors in osteoblastic cells. (10) Mechanistic support also exists for a beneficial effect of higher flavonol intake on BMD; quercetin and kampferol have been found to inhibit bone loss in ovariectomized mice (8) via a range of potential mechanisms including effects on osteoclast differentiation involving NF-kB and AP-1 induction by RANKL, (13,15) stimulating alkaline phosphatase activity, promoting osteoblast activity, and upregulating bone sialoprotein gene promoter. (16,18) We found an association between a higher flavonol intake and higher BMD at the spine, similar to findings from a previous study, which had only included intakes of a few flavonols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7,(10)(11)(12)33,34) In another study, the flavanone glycoside, naringin, protected against ovariectomy-induced bone loss, potentially mediated through ligand-independent activation of estrogen receptors in osteoblastic cells. (10) Mechanistic support also exists for a beneficial effect of higher flavonol intake on BMD; quercetin and kampferol have been found to inhibit bone loss in ovariectomized mice (8) via a range of potential mechanisms including effects on osteoclast differentiation involving NF-kB and AP-1 induction by RANKL, (13,15) stimulating alkaline phosphatase activity, promoting osteoblast activity, and upregulating bone sialoprotein gene promoter. (16,18) We found an association between a higher flavonol intake and higher BMD at the spine, similar to findings from a previous study, which had only included intakes of a few flavonols.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) Flavonoids have the potential to affect bone health; certain classes of flavonoid compounds have been shown to prevent bone loss in ovariectomized animal models (7)(8)(9)(10) and to improve bone quality and strength in orchidectomized rats. (11,12) A number of potential mechanisms have been proposed, including effects on osteoclast differentiation via mechanisms involving NF-kB and AP-1 induced by receptor activator of NF-kB ligand (RANKL) in vitro, (13)(14)(15) stimulating alkaline phosphatase activity or promoting osteoblast activity and upregulating bone sialoprotein gene promoter. (16)(17)(18) Most previous research examining flavonoids and bone health, including randomized controlled trials (RCTs), have focused on the isoflavone subclass with equivocal results.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have clearly shown that quercetin acts as a potent pleiotropic modulator in several physiological functions, showing different activities such as anti-proliferative effect in numerous cell lines [6,7], pro-apoptotic effect in lung carcinoma cell lines [8], and inhibitory effect of osteoclastic differentiation [9]. It is important to note that when the glycosylated forms of quercetin are assayed, there is usually a loss of activity in these effects in comparison with those obtained with the aglycone, due to the presence of the sugar moiety in the flavonoid structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin as a naturally occurring flavonoid protects cells against oxidative stress [7,8]. Several studies have shown that quercetin in its free or glycosylated form modulates certain physiological functions with potent antiproliferative effects in numerous cell lines [9,10], pro-apoptotic effect in lung carcinoma cell lines [11], and inhibitory effect of bone metabolism [12].…”
Section: Introductionmentioning
confidence: 99%